Sabine Schrenk, Textilien des Mittelmeerraumes aus spatantiker bis fruhislamischer Zeit - Maraković, Nikolina (Array, 2005)
The article is a review of the catalogue of the textile objects from Abbeg-Stiftung. It presents the organization and quality of the catalogue, concentrating on some of the main problems and topics.